(untitled) (Journal of Governance and Development (JGD), 2007)
The process of urbanisation has brought forth challenges that need to be addressed by governments of nations who are trying to manage their cities and improve the quality of urban living of their communities. The phenomenon from progressive urbanisation and growth of towns and cities is the acceleration in economic development and social changes in the urban centres. Such urban activities have influenced the development and growth of new towns and conurbations giving rise to a host of new activities encompassing economics, environment, governance, land use, infrastructure and technology. There is need to recognise the emergence of these urban issues and their impact upon the development of a nation. Malaysia is a classic case of a nation challenged with the process of rapid urbanisation and this paper explores the country’s efforts at addressing and coordinating urban development between the various sectors and agencies involved. Initial observations reveal that to meet the aspirations of communities and the plan for new development in urban areas, there ought to exist engagement, consolidation and empowerment. In addition, urban centres need to identify niche areas of economic activities and place emphasis on productivity, competitiveness and quality.